1999
DOI: 10.1016/s0090-4295(98)00567-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of finasteride on prostate tissue composition

Abstract: Objectives. To determine the long-term effects of finasteride treatment on prostate tissue composition; to relate these effects to clinical outcomes; and to test the hypothesis that finasteride exerts a selective or preferential action on the transition zone. Methods. Nineteen men with symptomatic benign prostatic hyperplasia (BPH) who completed a 6-month double-blind trial of finasteride were enrolled in a 24-month open-label extension study of drug responders. Magnetic resonance imaging and prostate biopsy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 31 publications
3
42
0
3
Order By: Relevance
“…The volume fraction occupied by glandular lumen in prostate tissue varies between the anatomic zones and between patients. Studies incorporating quantitative morphology have reported values between 20% and 40% in normal glandular prostate tissue (17,18). These numbers are similar to the signal fractions found in our study, supporting the notion of prostate fluid being the source of the long T2 component.…”
Section: Volunteer Studysupporting
confidence: 90%
“…The volume fraction occupied by glandular lumen in prostate tissue varies between the anatomic zones and between patients. Studies incorporating quantitative morphology have reported values between 20% and 40% in normal glandular prostate tissue (17,18). These numbers are similar to the signal fractions found in our study, supporting the notion of prostate fluid being the source of the long T2 component.…”
Section: Volunteer Studysupporting
confidence: 90%
“…Tempany et al (14) used 1.5 Tesla (T) MRI and found a larger reduction in the peripheral zone, although it was not statistically significant. Other longitudinal, double-blinded studies using volumetric assessment with TRUS found decreases in both peripheral zone volume and transition zone volume (10,15,16). Furthermore, one of these studies detected a significant positive correlation between transition zone index (i.e., the transition zone volume as a percentage of the whole prostate gland) and the change in prostate volume for patients on dutasteride (10).…”
Section: Role Of Prostatic Volume Determination In Bph Managementmentioning
confidence: 95%
“…The impact of 5ARIs on prostatic tissue quality is not well understood but 5ARIs are known to affect the glandular to stromal ratio with an overall reduction in glandular tissue [27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…Dual irrigation is used to keep the bladder full and to improve visualization. Irrigation was placed approximately [24][25][26][27][28][29][30] inches above the level of the bladder. Unusually tough prostatic tissue (termed "beach balls") may occasionally be encountered during enucleation which can prolong morcellation time.…”
Section: Description Of Proceduresmentioning
confidence: 99%